Isolation of Phosphate Recruiting Endophytic Fungi from the Leaves of the Symphony Fern Plant (Cibotium Barometz (L.) J.Sm) - Safira Nurul Fadila; Dezi Handayani; Azwir Anhar; Violita Violita (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Phosphate is one of the elements needed in large quantities for plant growth and development. Phosphate can be found in soil, but generally in the form of bound phosphate, so that it cannot be used by plants. Generally, farmers overcome the availability of phosphate for plants using phosphate fertilizer, but this method is not effective. Another alternative is needed to overcome the availability of phosphate in the soil. One alternative that can be used is to use phosphate-solubilizing endophytic fungi. Phosphate-solubilizing endophytic fungi can be isolated from the leaves of the Simpei fern (Cibotium barometz (L.) J.Sm.). The Simpei fern plant contains organic acids, so endophytic fungi isolated from the leaves of the Simpei fern plant are expected to produce the same organic acids and be able to dissolve phosphate. Therefore, this study aims to determine the phosphate solubilizing activity of the leaves of the Simpei fern plant. The samples used were the leaves of the symbiotic fern. The fungus obtained was tested using Pikovskaya medium. Phosphate solubilizing activity is characterized by the formation of a clear zone around the fungus colony. Six isolates of endophytic fungi from the Simpei fern plant were obtained, namely D1, D2, D3, D4, D5, and D6. Two isolates have phosphate solubilizing activity, namely isolates D2 and D4. The highest phosphate solubility index was shown by isolate D2 on the first day of 0.8. The phosphate solubility index of all isolates is low. Key words: endophytic fungi, fosfat, isolated, activity